Daily Activity Based Learning combined Contextual Teaching and Learning Approach in the Animal Anatomy and Development Course to Improve Critical Thinking Skills - Riska Septia Wahyuningtyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Learning in the 21st century requires lecturers to be more creative in finding learning models that can be carried out by students with online learning limitations. Appropriate learning is through a daily activity based learning model combined with 7 contextual teaching and learning standards. The research method in this study uses the classroom action research method. The data analysis technique will use SPSS with the T test. The research results show that Daily activity based learning (DABL) can improve critical thinking skills based on the posttest in each cycle. Student scores increased from pretest to posttest cycle I, and from posttest cycle I to posttest cycle II. This is proven by the average pretest score for cycle I increasing from 62.76 to 74.21. Then the post-test value from cycle I to post-test cycle II also increased from 74.21 to 80.26. After the T test with SPSS, the increase in value shows a significant difference because the T test value is <0.05, which shows that there is a real difference between the results of the pretest, posttest I and posttest II. Daily activity-based learning (DABL) can improve critical thinking skills based on posttests in each cycle because there is a combination of learning steps which include modeling, learning communities, constructivism, inquiry, questioning, reflection and authentic assessment. Learning with the Daily Activity Based Learning model is related to the achievement of SDGs no 4 Quality education which requires students to have critical thinking skills to carry out sustainable development actions.